Preparing Retro Arcade Fighting Game Asset Design - Arifin, Zainal; Waksito, Alan Zulfikar; Firdaus, Muhammad Bambang; Puspitasari, Novianti (JAIA - Journal of Artificial Intelligence and Applications, 2023)
Games are increasingly popular in Indonesia because of the many things that make them exciting, such as esports. The Fighting Game genre is one that contains a fight between two characters in a place or arena with the aim of depleting the opponent's HP (health points). Fighting Games use 2-dimensional and/or 3-dimensional graphics where players play characters who can punch, jump or squat when fighting characters. other. In designing video game assets, researchers used the GDLC (Game Development Life Cycle) methodology so that this research proceeded systematically and focused on the design of game asset components. In designing a video game there are many elements, in this research the author focuses more on the control assets of the Combo Hit System on a game character called Brawl Tale.